CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Status, trends and drivers of kelp forests in Europe: an expert assessment - R. M. Araújo; J. Assis; R. Aguillar; L. Airoldi; I. Bárbara; I. Bartsch; T. Bekkby; H. Christie; D. Davoult; S. Derrien-Courtel; C. Fernandez; S. Fredriksen; et al. (Biodiversity and Conservation, 2016)

Sinks for nitrogen inputs in terrestrial ecosystems: a meta‐analysis of 15 N tracer field studies - P. H. Templer; M. C. Mack; F. S. Chapin III; L. M. Christenson; J. E. Compton; H. D. Crook; W. S. Currie; C. J. Curtis; D. B. Dail; C. M. D'Antonio; B. A. Emmett; H. E. Epstein; et al. (Ecology, 2012)
Effects of anthropogenic nitrogen (N) deposition and the ability of terrestrial ecosystems to store carbon (C) depend in part on the amount of N retained in the system and its partitioning among plant and soil pools. We conducted a meta‐analysis of studies at 48 sites across four continents that used enriched 15 N isotope tracers in order to synthesize information about total ecosystem N retention (i.e., total ecosystem 15 N recovery in plant and soil pools) across natural systems and N partitioning among ecosystem pools. The greatest recoveries of ecosystem 15 N tracer occurred in shrublands (mean, 89.5%) and wetlands (84.8%) followed by forests (74.9%) and grasslands (51.8%). In the short term ( 15 N tracer application), total ecosystem 15 N recovery was negatively correlated with fine‐root and soil 15 N natural abundance, and organic soil C and N concentration but was positively correlated with mean annual temperature and mineral soil C:N. In the longer term (3–18 months after 15 N tracer application), total ecosystem 15 N retention was negatively correlated with foliar natural‐abundance 15 N but was positively correlated with mineral soil C and N concentration and C : N, showing that plant and soil natural‐abundance 15 N and soil C:N are good indicators of total ecosystem N retention. Foliar N concentration was not significantly related to ecosystem 15 N tracer recovery, suggesting that plant N status is not a good predictor of total ecosystem N retention. Because the largest ecosystem sinks for 15 N tracer were below ground in forests, shrublands, and grasslands, we conclude that growth enhancement and potential for increased C storage in aboveground biomass from atmospheric N deposition is likely to be modest in these ecosystems. Total ecosystem 15 N recovery decreased with N fertilization, with an apparent threshold fertilization rate of 46 kg N·ha −1 ·yr −1 above which most ecosystems showed net losses of applied 15 N tracer in response to N fertilizer addition.

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Assessment ofsolatium hougasii in Washington and Mexico as a source of resistance to late blight - D. A. Inglis; C. R. Brown; B. G. Gundersen; L. D. Porter; J. S. Miller; D. A. Johnson; H. Lozoya-Saldaña; K. G. Haynes (American Journal of Potato Research, 2007)

Maximum rates of N 2 fixation and primary production are out of phase in a developing cyanobacterial bloom in the Baltic Sea - J. R. Gallon; A. M. Evans; D. A. Jones; P. Albertano; R. Congestri; B. Bergman; K. Gundersen; K. M. Orcutt; K. von Bröckel; P. Fritsche; M. Meyerhöfer; K. Nachtigall; et al. (Limnology and Oceanography, 2002)
Although N 2 ‐fixing cyanobacteria contribute significantly to oceanic sequestration of atmospheric CO 2 , little is known about how N 2 fixation and carbon fixation (primary production) interact in natural populations of marine cyanobacteria. In a developing cyanobacterial bloom in the Baltic Sea, rates of N 2 fixation (acetylene reduction) showed both diurnal and longer‐term fluctuations. The latter reflected fluctuations in the nitrogen status of the cyanobacterial population and could be correlated with variations in the ratio of acetylene reduced to 15 N 2 assimilated. The value of this ratio may provide useful information about the release of newly fixed nitrogen by a cyanobacterial population. However, although the diurnal fluctuations in N 2 fixation broadly paralleled diurnal fluctuations in carbon fixation, the longer‐term fluctuations in these two processes were out of phase.

Polychlorinated Biphenyls and Chlordane in the Gonads of Paddlefish, Polyodon spathula, from the Ohio River - D. T. Gundersen; M. D. Krahling; J. J. Donosky; R. G. Cable; S. D. Mims (Bulletin of Environmental Contamination and Toxicology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Subacute toxicity of the water-soluble fractions of Kuwait crude oil and partially combusted crude oil on Menidia beryllina and Palaemonetes pugio - D. T. Gundersen; S. W. Kristanto; L. R. Curtis; S. N. Al-Yakoob; M. M. Metwally; D. Al-Ajmi (Archives of Environmental Contamination and Toxicology, 1996)